Systematic Identification of Molecular Links between Core and Candidate Genes in Breast Cancer. Issue 6 (27th March 2015) - Arroyo, Rodrigo; Suñé, Guillermo; Zanzoni, Andreas; Duran-Frigola, Miquel; Alcalde, Víctor; Stracker, Travis H.; Soler-López, Montserrat; Aloy, Patrick
Abstract: Despite the remarkable progress achieved in the identification of specific genes involved in breast cancer (BC), our understanding of their complex functioning is still limited. In this manuscript, we systematically explore the existence of direct physical interactions between the products of BC core and associated genes. Our aim is to generate a protein interaction network of BC-associated gene products and suggest potential molecular mechanisms to unveil their role in the disease. In total, we report 599 novel high-confidence interactions among 44 BC core, 54 BC candidate/associated and 96 newly identified proteins. Our findings indicate that this network-based approach is indeed a robust inference tool to pinpoint new potential players and gain insight into the underlying mechanisms of those proteins with previously unknown roles in BC. To illustrate the power of our approach, we provide initial validation of two BC-associated proteins on the alteration of DNA damage response as a result of specific re-wiring interactions. Overall, our BC-related network may serve as a framework to integrate clinical and molecular data and foster novel global therapeutic strategies. Graphical Abstract: Highlights: We report 599 novel interactions that complement the BC-associated network. These interactions link BC causative and susceptibility genes. Of these novel interactions, 108 involve 76 genes that have not been related to BC. We provide initial validations for six genes involved in DNA damage response.